Maternal and child health care in an underprivileged area of Bangalore city: Identifying the gaps in the continuum of care - Avita R Johnson; Sulekha Thimmaiah; Sumithra Selvam; Prem Mony; Arvind Kasthuri (Global Journal of Medicine and Public Health, 2024)
Background